Peningkatan Minat Baca Siswa dengan Pojok Baca untuk Siswa Sekolah Dasar - Asyafina Rosyada; Ahmad Furkoni Hasyim (Yayasan Citra Dharma Cindekia, 2024)
School literacy activities are one of the government programs implemented to increase student interest in learning in Indonesia. This research focuses on interest in reading and literacy culture based on the main data obtained showing that students' interest in reading at SDN Maor is still relatively low. The aim of this research is to provide students with an overview of the importance of literacy activities in increasing interest in reading. Data collection techniques use observation and interviews. Data analysis uses descriptive data analysis. The results of the research stated that the literacy corner was able to increase interest in reading in grades V and VI of Maor State Elementary School. Several roles of the reading corner can increase students' interest in reading in elementary schools. This research can be concluded that reading corners really help foster students' interest in reading in class, the role of reading corners in growing students' interest in reading, namely, as a facilitator for reading places, as nearby reading material, a comfortable reading place and a reading place that attracts attention, so that from several This role helps foster interest in reading in grades V and VI students at Maor State Elementary School. Therefore, it is important to increase literacy in Indonesia for the future of the nation's future with the knowledge gained from reading